The role of cognitive and affective trust in the relationship between organizational justice and organizational citizenship behavior: a conceptual framework - Prerna Chhetri (Business: Theory and Practice, 2014)
The current paper develops a conceptual framework to investigate the role of the two bases of trust (cognitive and affective), and foci of trust (supervisor and management) in the relationship between organizational justice and organizational citizenship behavior. The purpose of the current paper is to propose a framework for the multi dimensionality of trustcognitive and affective trust, in mediating the relationship between organizational justice and organizational citizenship behavior. It is proposed that cognitive trust in management will mediate the relationship between distributive justice, and OCBO and between procedural justice and OCBO. It is also proposed that affective trust in immediate supervisor will mediate the relationship between Interactional Justice and citizenship behavior directed towards the individual.The paper attempts to understand if the bases of trust (cognitive and affective) and foci of trust (trust in management and trust in immediate supervisor) will answer the call of researchers for understanding the reason for the different impact of justice on OCB.